Rights of convicted minors: features of ensuring and implementing them during martial law in Ukraine - O. M. Humin (Науковий вісник Ужгородського національного університету. Серія Право)
The article is devoted to the necessity of ensuring and implementing the rights of convicted minors during martial law in Ukraine, which is an important feature of a legal state and a democratic society.